Scale Banking for Patient‐Reported Outcome Measures That Measure Functioning in Rheumatoid Arthritis: A Daily Activities Metric. Issue 4 (13th February 2022) - Prodinger, Birgit; Coenen, Michaela; Hammond, Alison; Küçükdeveci, Ayşe A.; Tennant, Alan
Abstract : Objective: Functioning is an important outcome for the management of rheumatoid arthritis (RA). Heterogeneity of respective patient‐reported outcome measures (PROMs) challenges direct comparisons between their results. This study aimed to standardize reporting of such PROMs measuring functioning in RA to facilitate comparability. Methods: Common‐item nonequivalent group design with the Health Assessment Questionnaire (HAQ) as a common scale across data sets from various countries (including the UK, Turkey, and Germany) to establish a common metric was used. Other PROMs included are the physical function items of the Multidimensional HAQ (MDHAQ), the Disabilities of the Arm, Shoulder, and Hand questionnaire, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), the World Health Organization Disability Assessment Schedule II (WHODAS II), the Medical Outcomes Study Short Form 36 (SF‐36) health survey, and 4 short forms (20, 10, 6, and 4 physical function items) from the Patient‐Reported Outcomes Measurement Information System. As the HAQ includes mobility, self‐care, and domestic life items, this study focuses on these 3 domains. PROMs were described using standard error of measurement (SEM) and smallest detectable difference (SDD). A Rasch measurement model was used to create the common metric. Results: The range of the SEM was 0.2 (MDHAQ) to 7.4 (SF‐36 health survey physical functioning domain). The SDD revealed a range from 9.7% (WOMAC rating scale) to 33.5% (WHODAS physical functioning domain). PROMs co‐calibration revealed fit to the Rasch measurement model. A transformation table was developed to allow exchange between PROM scores. Conclusion: Scores between the daily activity PROMs commonly used in RA can now be compared. Factors such as SEM and SDD help to determine the choice of a PROM in clinical practice and research.